Efficacy and Safety of Bone Marrow-Derived Mesenchymal Stem Cells for Chronic Antibody-Mediated Rejection After Kidney Transplantation- A Single-Arm, Two-Dosing-Regimen, Phase I/II Study - Wei, Yongcheng; Chen, Xiaoyong; Zhang, Huanxi; Su, Qun; Peng, Yanwen; Fu, Qian; Li, Jun; Gao, Yifang; Li, Xirui; Yang, Shicong; Ye, Qianyu; Huang, Huiting; et al. (Frontiers in Immunology, 2021)
Objective: To investigate the efficacy and safety of bone marrow-derived mesenchymal stem cells (BM-MSCs) on chronic active antibody-mediated rejection (cABMR) in the kidney allograft. Methods: Kidney recipients with biopsy-proven cABMR were treated with allogeneic third-party BM-MSCs in this open-label, single-arm, single-center, two-dosing-regimen phase I/II clinical trial. In Regimen 1 (n=8), BM-MSCs were administered intravenously at a dose of 1.0×106 cells/kg monthly for four consecutive months, while in Regimen 2 (n=15), the BM-MSCs dose was 1.0×106 cells/kg weekly during four consecutive weeks. The primary endpoints were the absolute change of estimated glomerular filtration rate (eGFR) from baseline (delta eGFR) and the incidence of adverse events associated with BM-MSCs administration 24 months after the treatment. Contemporaneous cABMR patients who did not receive BM-MSCs were retrospectively analyzed as the control group (n =30). Results: Twenty-three recipients with cABMR received BM-MSCs. The median delta eGFR of the total BM-MSCs treated patients was -4.3 ml/min per 1.73m2 (interquartile range, IQR -11.2 to 1.2) 2 years after BM-MSCs treatment (P=0.0233). The median delta maximum donor-specific antibody (maxDSA) was -4310 (IQR -9187 to 1129) at 2 years (P=0.0040). The median delta eGFR of the control group was -12.7 ml/min per 1.73 m2 (IQR -22.2 to -3.5) 2 years after the diagnosis, which was greater than that of the BM-MSCs treated group (P=0.0342). The incidence of hepatic enzyme elevation, BK polyomaviruses (BKV) infection, cytomegalovirus (CMV) infection was 17.4%, 17.4%, 8.7%, respectively. There was no fever, anaphylaxis, phlebitis or venous thrombosis, cardiovascular complications, or malignancy after BM-MSCs administration. Flow cytometry analysis showed a significant decreasing trend of CD27-IgD- double negative B cells subsets and trend towards the increase of CD3+CD4+PD-1+/lymphocyte population after MSCs therapy. Multiplex analysis found TNF-α, CXCL10, CCL4, CCL11 and RANTES decreased after MSCs treatment. Conclusion: Kidney allograft recipients with cABMR are tolerable to BM-MSCs. Immunosuppressive drugs combined with intravenous BM-MSCs can delay the deterioration of allograft function, probably by decreasing DSA level and reducing DSA-induced injury. The underlying mechanism may involve immunomodulatory effect of MSCs on peripheral B and T cells subsets.